A critical literature review of dyadic web‐based interventions to support cancer patients and their caregivers, and directions for future research. Issue 1 (19th December 2019) - Luo, Xingjuan; Gao, Lihong; Li, Jieyu; Lin, Yi; Zhao, Jie; Li, Qiuping
Abstract: Objective: With the rapid development of the Internet, e‐health interventions are becoming popular and are showing positive impacts. Cancer affects not only patients but also their caregivers, leading to a recognition that cancer patient–caregiver dyads cope with cancer as a unit rather than as individuals. The objectives of this paper are to explore web‐based interventions for cancer patient–caregiver dyads coping with cancer from the aspects of intervention content, delivery format, outcome measurements, and outcomes and to provide recommendations on developing patient‐caregiver dyadic web‐based interventions for future research. Methods: Literature focused on cancer patient–caregiver dyadic web‐based interventions, published in English or Chinese from the launch of five databases (CINAHL, PsycINFO, EMBase, Medline, Science Citation Index Expanded) to April 2019, was systematically searched. Manual searching through the references of full‐text articles was also conducted. Results: Of a total of 812 articles, 17 articles met the inclusion criteria. The content of these web‐based dyadic interventions mainly included information support, communication and support, skills‐building, and psycho‐education. These web‐based interventions reported a small to large positive impact on patients with cancer and their caregivers in terms of physical health ( d = 0.17‐0.75), psychological health ( d = 0.04‐0.80), overall quality of life ( d = 0.20‐0.68), and dyadic relationship ( d = 0.30‐0.95). Conclusions: Web‐based dyadic interventions can be designed for tailored content, which benefits both patients and their caregivers. Future research on cancer patient–caregiver web‐based interventions should be conducted in diverse cultures.